A new species of freshwater crab of the genus Kingsleya Ortmann, 1897 (Crustacea: Brachyura: Pseudothelphusidae) from Amazonia, Brazil - Pedraza, Manuel; Tavares, Marcos (Zootaxa, 2015)
A new species of freshwater crab, Kingsleya celioi, from the Brazilian Amazon (Pará State) is described and illustrated. The new species can be easily separated from their congeners by a suite of morphological characters, including the apical plate of the first gonopod large, widest medially in abdominal view, with single large spine-like outgrowth in midlength of mesial margin; distal, proximal lobes of apical plate unequal in size, distal lobe largest, tapering distally in lateral view.